Community Perceptions of Village Health Workers in Kisoro, Uganda - Crystal Zheng; Joanne Anthonypillai; Sam Musominali; Gloria Fung Chaw; Gerald Paccione (Ubiquity Press, 2021)
Background: Village health workers (VHWs) can serve as a valuable resource to address public health needs in resource-limited settings such as Uganda. However, the successful implementation of VHW programs can be limited by poor acceptability among community members. Kisoro District Hospital (KDH) in Kisoro District, Uganda operates a VHW program and, at the time of the study, was expanding its services to 11 additional villages. Objective: The objective of this study was to evaluate community perceptions of VHWs in villages of Kisoro District with no prior exposure to the KDH VHW program in order to improve community acceptance when expanding the program to additional villages. Methods: We administered surveys to 658 community members from 11 villages to evaluate their perceptions of VHWs prior to receiving VHW services. Additionally, we conducted focus group discussions among 97 participants to explore perceptions of VHWs in further depth. Findings: Community members were generally accepting of VHWs. They preferred that VHWs provide both curative and preventive services across a broad range of health domains as opposed to a single disease. Expectations of the responsibilities of a VHW were influenced by agricultural occupational and household responsibilities, particularly for women. Participants expressed a preference to be actively involved in the selection and oversight of VHWs and that VHWs receive compensation. Conclusions: 1) Community members' expectations of VHWs are shaped by environmental, cultural, and social factors. 2) Active community engagement in the VHW program is key. 3) Aligning a VHW program with community perceptions may improve acceptance, in turn influencing effectiveness and sustainability. These findings were used to expand the KDH VHW Program into the participating villages in a manner consistent with community preferences. Our findings may provide guidance on enhancing the uptake of community-based VHW programs for VHW stakeholders and policymakers in other settings.